Lactic Acid: A Novel Signaling Molecule in Early Pregnancy? - Ma, Li-Na; Huang, Xiao-Bo; Muyayalo, Kahindo P.; Mor, Gil; Liao, Ai-Hua (Frontiers in Immunology, 2020)
Aerobic glycolysis is a recognized feature shared by tumors, leading to the accumulation of lactic acid in their local microenvironments. Like the tumors, the blastocysts, placenta, trophoblasts and decidual immune cells can also produce a large amount of lactic acid through aerobic glycolysis during the early pregnancy. Moreover, the placenta express the transporters of the lactic acid. While several studies have described the role of lactic acid in the tumormicroenvironment, especially lactic acid’s modulation of immune cells, the role of lactic acid produced during pregnancy is still unclear. In this paper, we reviewed the scientific evidence detailing the effects of lactic acid in the tumor microenvironment. Based on the influence of the lactic acid on immune cells and tumors, we proposed that lactic acid released in the unique uterine environment could have similar effects on the trophoblast cells and immune cells during the early pregnancy.